Pengaruh Kombinasi Pijat Oksitosin dan Jus Wortel terhadap Peningkatan Produksi Air Susu Ibu (ASI) pada Ibu Postpartum Primipara - Perintisari, Dian Hepy; Pramono, Joko Sapto; Suryani, Heni (JIDAN Jurnal Ilmiah Bidan, 2023)
Background: Exclusive breastfeeding for 0-6 months in Indonesia is 50.67%. The problem of breastfeeding in primiparous mothers is the lack of breast milk production after giving birth. Efforts that can be made are oxytocin massage and giving carrot juice. Objective: to determine the effect of a combination of oxytocin massage and carrot juice on increasing breast milk production in primiparous postpartum mothers at PMB Dian Tenggarong. Method: Research design true experimental with pretest-posttest with control group design. The research sample was all postpartum primigravida mothers at PMB Dian Tenggarong totaling 18 people for each group using the techniqueconsequtive sampling. The independent variables are oxytocin massage and carrot juice. The dependent variable of the research is breast milk production. Research instruments include oxytocin massage SOPs, measuring cups, cake scales, and observation sheets. The statistical test used is Test Wilcoxon. Results: The statistical test results explain The effect of a combination of oxytocin massage and carrot juice on increasing breast milk production in primiparous postpartum mothers at PMB Dian Tenggarong. Researchers recommend that the public and health workers provide oxytocin massage treatment and carrot juice for breastfeeding mothers who experience breastfeeding problems in the form of low breast milk production.